"I'm not like others": stigma navigation by people who inject drugs in Vietnam. (2nd January 2022) - Trang, Nguyen Thu; Jauffret-Roustide, Marie; Giang, Le Minh; Visier, Laurent
Abstract: Background: People who inject drugs are subjected to great stigmatization in many parts of the world. How they deal with stigma is closely linked to how stigma means to them. Understanding the strategies individuals employ to cope with these negative attitudes and what resources they mobilize in this process gives useful insights for clinical work and policy development. Methods: We conducted 12 months of field observation in 2017 and 2018 and 54 in-depth interviews with people who inject drugs in Haiphong, Vietnam. Grounded theory underpinned our sampling and data analysis. Results: The strategies participants used to manage stigma were both information and tension management. Many participants not only concealed their drug use but actively cultivated a pro-social image based on Vietnamese cultural virtues such as selflessness, hard work or harmonious living with others. Participants withdrew from social relationships to distance themselves from the stereotype of a money-begging drug user. They used techniques of neutralization to emphasize their good character and reframe their drug-related issues in a different light in order to negotiate their social status with their interlocutors. Conclusion: People who inject drugs endorse the same social values and aspirations as nonusers. A good support structure and resources could help them to cope more effectively with stigma.